Modelling of cloud based online access system for solar charge controller - S.P.M. Sharma B, S; Ravishankar Kamath, H; Siva Brahmaiah Rama, V (International Journal of Engineering and Technology, 2018)
In the current scenario, the considerable necessity of industry is to concatenate heterogeneous hardware components to the cloud based online access system for monitoring and identifying their behavior over a period. Every cloud computing is provided with a secured login credentials for limited access. The main objective of this paper is to record and transmit the readings of the instruments (Solar Charge Controller) to IoT which deals with establishing the suitable Web application on the cloud for Data logging and diagnostics. Using microcontroller information can be transmitted wirelessly with the help of Ethernet or Wi-Fi module. Some of the electrical devices can direct certain parameters to the microcontroller which are handled with the help of Ethernet or Wi-Fi module and connected to the cloud based system which may lessen the overall memory squandered. An attempt has been made to know the status of devices through PC/Laptop/Mobile/Tablet at any place while connected to cloud computing services.